2019
DOI: 10.1111/irv.12649
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of influenza vaccine during pregnancy: A systematic review and meta‐analysis

Abstract: Background Pregnant women have an elevated risk of illness and hospitalisation from influenza. Pregnant women are recommended to be prioritised for influenza vaccination during any stage of pregnancy. The risk of seasonal influenza varies substantially throughout the year in temperate climates; however, there is limited knowledge of how vaccination timing during pregnancy impacts the benefits received by the mother and foetus. Objectives To compare antenatal vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 66 publications
(235 reference statements)
5
58
0
Order By: Relevance
“…Most studies have shown that the antibody response to influenza vaccine is similar in pregnant and non-pregnant women (Haberg et al, 2013;Mak et al, 2008), although there is some debate as to the optimal timing of vaccination in pregnancy. A meta-analysis of 16 studies found that the response to influenza vaccination was 1.33-1.96-fold higher in women vaccinated during the third trimester of pregnancy than at earlier time points, with evidence suggesting that vaccination later in pregnancy increased antibody transfer to the foetus by 1.21-1.64-fold (Cuningham et al, 2019). However, earlier vaccination provides longer protection against influenza for the pregnant woman, and averting infection early in pregnancy may have positive benefits for the foetus.…”
Section: Immunogenicity Of Influenza Vaccination In Pregnant Women and Antibodies In Newborns And Infantsmentioning
confidence: 99%
“…Most studies have shown that the antibody response to influenza vaccine is similar in pregnant and non-pregnant women (Haberg et al, 2013;Mak et al, 2008), although there is some debate as to the optimal timing of vaccination in pregnancy. A meta-analysis of 16 studies found that the response to influenza vaccination was 1.33-1.96-fold higher in women vaccinated during the third trimester of pregnancy than at earlier time points, with evidence suggesting that vaccination later in pregnancy increased antibody transfer to the foetus by 1.21-1.64-fold (Cuningham et al, 2019). However, earlier vaccination provides longer protection against influenza for the pregnant woman, and averting infection early in pregnancy may have positive benefits for the foetus.…”
Section: Immunogenicity Of Influenza Vaccination In Pregnant Women and Antibodies In Newborns And Infantsmentioning
confidence: 99%
“…More research studies on this subject could result in the development of future recommendations about the optimal period of time for immunization, (pre-conception, during pregnancy or postpartum) and the most cost-effective professionals, not only in the vaccination, but also in the monitoring and advice phases [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review and meta-analysis found that vaccinating women later in pregnancy, at least 15 days before delivery, results in higher influenza-specific maternal antibody concentrations at birth and thus transfer of more antibodies to the unborn child. On the other hand, vaccinating earlier in pregnancy will provide protection against influenza during a longer proportion of the pregnancy, which is beneficial for the pregnant women, but may increase the probability that protection does not last until delivery and that consequently protection is not transferred to the offspring [66]. Additionally, safety data on influenza vaccination during the first trimester of pregnancy are lacking.…”
Section: Influenzamentioning
confidence: 99%